The impact of income and asset diversification in banks performance: evidence from the euro area - Barata, Sara Isabel das Neves (2017)
This dissertation aims to provide an explanation on the research regarding the issue of banks’ activity and source of income specialization versus diversification. We examine the existing theories and empirically study the effect of activity and source of income diversification effect on performance, risk and market valuations on the Euro Area banks’. Our sample was constructed by gathering financial data from 2,062 Euro Area banks between the years of 2000-2014. The research study is centred on the potential to create revenue outgrowth through diversification and to further obtain a conclusion on whether diversification is beneficial or armful for banks. The main conclusions are that income diversification tends to improve the risk-return relationship, while the asset diversification worsens this relationship. Controversially, it is observable that the increase of income diversification increases the non-performing loans risk, analyzed as a standalone measure, and the asset diversification decreases this risk.